A cross-country comparison of labor market frictions - Geert Ridder; Gerard J. van den Berg (Institute for Labour Market Policy Evaluation (IFAU), 2002)
In this paper we define and estimate measures of labor market frictions using data on job durations. We compare different estimation methods and different types of data. We propose and apply an unconditional inference method that can be applied to aggregate duration data. It does not require wage data, it is invariant to the way in which wages are determined, and it allows workers to care about other job characteristics. The empirical analysis focuses on France, but we perform separate analyses for the USA, the UK, Germany and the Netherlands. We quantify the monopsony power due to search frictions and we examine the policy effects of the minimum wage, unemployment benefits and search frictions.
Keywords: J31; J42; J63; J68; 330; Wages; search frictions; cross-country comparisons; monopsony power; minimum wage; job search; mobility; labour market policy